Defibrotide in hematopoietic stem cell transplantation: A multicenter survey study of the Spanish Hematopoietic Stem Cell Transplantation Group (GETH). (30th March 2021) - González Vicent, Marta; Díaz de Heredia, Cristina; González de Pablo, Jesús; Molina, Blanca; Regueiro, Alexandra; Pérez Martinez, Antonio; Palomo, Pilar; López Corral, Lucía; García, Estefanía; Fernández, José María; Pérez, Ariadna; Jiménez, María José; et al.
Abstract: Background: Defibrotide is approved in European Union for the treatment of severe sinusoidal obstruction syndrome (SOS) after HSCT. However, it has also been used for SOS prophylaxis, moderate SOS and in other complications such as transplant‐associated thrombotic microangiopathy (TAM). The objective of this study was to evaluate current uses, effectiveness and safety of defibrotide in patients with HSCT. Methods: This multicenter, retrospective study included patients treated with defibrotide for any indication at 28 HSCT centers of the Grupo Español de Trasplante Hematopoyetico (GETH) including the pediatric subgroup Grupo Español de Trasplante de Medula en Niños (GETMON). Results: Three hundred and eighty eight patients treated with defibrotide between January 2011 and December 2018 were included. 253 patients were children, and 135 patients were adults. In total, 332 transplants were allogeneic, and the remainder were autologous. Main indications for defibrotide use were severe/very severe SOS in 173 patients, SOS prophylaxis in 135 patients, moderate SOS in 41 patients, TAM in six patients and suspected SOS in 33 patients. Overall survival (OS) at day +100 in the SOS prophylaxis group was 89% (95% CI, 87%‐91%). In the group of patients with moderate and severe/very severe SOS, the OS at day +100 was 80% (95% CI, 74%‐86%) and 62% (95% CI, 59%‐65%), respectively ( P  = .0015). With a longer follow‐up, median of 2 years (4 months– 7 years), OS was 63% (95% CI, 59%‐67%) in the SOS prophylaxis patients. OS for patients with moderate and severe/very severe SOS groups was 53% (95% CI, 47%‐61%) and 26% (95% CI, 22%‐30%), respectively ( P  = .006). 191 patients died, and SOS was the main cause of death in 23 patients (12%). Conclusions: Defibrotide has an acceptable safety profile with an improved response in severe/very severe SOS compared with historical controls, mainly in pediatric patients. Use of defibrotide for prophylaxis may improve prognosis of patients at high risk of complications due to endothelial damage such as those who receive a second transplant. SOS has an important impact on the HSCT long‐term survival, as can be concluded from our study.